Encalhes de Cetáceos ocorridos no período de 1984 a 2005 no litoral do Rio Grande do Norte, Brasil - Medeiros, Priscila Izabel Alves Pereira de (2006)
Strandings of live or dead aquatic mammals constitute an important instrument to provide information regarding the occurrence, biology and ecology of these species. The aim of this study was to register the stranded species of cetaceans, the frequency and the spatial-temporal distribution of theses strandings during the period of 1984 to 2005, in the coast of Rio Grande do Norte. Data was acquired through the monitoring of strandings in the north, north-west and south coast of RN, and through information obtained from institutions and newspaper archives of the State. A total of 122 strandings of cetaceans were registered along the coast of Rio Grande do Norte. Of the 14 species of cetaceans registered, four species had higher frequencies: Sotalia guianensis (n= 65), Steno bredanensis (n = 6), Globicephala macrorhynchus (n = 6) and Physeter macrocephalus (n = 7). Out of 118 strandings, 93 occurred in the south coast (78.8 %), 23 in the north coast (19.5%) and 2 (1.7%) in the north-west coast of the State. The highest frequency of strandings occurred during the months of August to March and the maximum number of strandings occurred from 2000 onwards, as a consequence of the intense monitoring of the Pequenos Cetáceos Project in Rio Grande do Norte